Seleção de plantas daninhas multiplicadoras de fungos ma e sua influência sobre a população micorrízica arbuscular em um solo com diferentes níveis de fósforo - Costa, Rogério Sebastião Corrêa da (1994)
The aim of this paper was to select weeds as host plants for inoculun production of indigenous and inoculated arbuscular mycorrhizal fungi and to verify its influence on the spore population of arbuscular mycorrhizal fungi and on growth of pepper (Capsicum annuum L.) in a soil with different levels of available phosphorus. Two experiments were conducted under greenhouse conditions at the Campus of the Universidade Federal do Ceará, BraziI. The experimental design was completely randomized and 5 repIicates in a crossed factorial 2x2x7 scheme. It was used a Gray Brown Podsol, not sterilized, with 173 and 5 mg/kg of available phosphorus. The weeds tested as host plants were brachiaria grass (Brachiaria decumbens Stapt), bahlagrass (Paspalum notatum Trin.), ginger grass (Paspalum maritimum Trin) and sedge (Cyperus sp.). The inoculation was carried out wlth Gigaspora margarita Becker e HalI before planting. The pepper plants were fertiIizaed weekly wlth Hewitt solution without phosphorus. Sixty days later the weeds and pepper were harvested and the following parameters were evaluated: shoot dry matter and shoot phosphorus content, soil phosphorus and sodium contents, soiI electrical conductance, root colonization, and number of spores per 100 grams of soil. The high level of phosphorus in soiI increased sporulation, root colonization, phosphorus contents and shoot dry matter of weeds and pepper. Inoculation increased spore the population of Gigaspora spp. In soil Brachiaria, ginger and bahlagrass and the mixture of grasses increased significantly the mycorrizal population, while the treatment wlth sedge showed inibitory effect on the spore population. The ginger grass showed to be an important arbuscular mycorrhizal propagative plant for the region.